THU0071 Protein Tyrosine Phosphatase Nonreceptor Type 2 (PTPN2) is an Important Regulator of Inflammation and Autophagy in Rheumatoid Arthritis. (23rd January 2014) - Aradi, B.; Kato, M.; Filková, M.; Kasper, S.; Klein, K.; Bader, M.; Scharl, M.; Michel, B. A.; Gay, R. E.; Buzás, E. I.; Gay, S.; Jüngel, A.
Abstract : Background: Recently we found that Protein Tyrosine Phosphatase Nonreceptor Type 2 (PTPN2) is involved in the apoptosis resistance of rheumatoid arthritis synovial fibroblasts (RASF). Objectives: Autophagy is strongly connected to apoptosis, and is activated via a series of phosphorylation events. We wanted to investigate whether PTPN2 plays a role in autophagy and inflammation in RASF. Methods: PTPN2 expression was analysed in synovial tissues by immunohistochemistry and real-time PCR. Transcription levels of PTPN2 were detected with or without tumor necrosis factor α (TNFα 10 ng/ml, 24 h), IL1β (1 ng/ml), LPS (100 µg/ml) and hypoxia (1%). PTPN2 protein levels were assessed by Western blotting. After silencing PTPN2 in RASF, commercially available ELISA was used to measure IL-6 and IL-8 in culture supernatants. TNF-related apoptosis-inducing ligand (TRAIL, 20 ng/ml, 24 h) induced apoptosis was measured after staining with AnnexinV using flow cytometry. Autophagy was induced by Thapsigargin (5 µM, 24h). Western blot was used to measure LC3B-I and LC3B-II. Results: In the lining and the sublining layer of RA synovial tissue, a stronger PTPN2 staining was detected by immunohistochemistry compared to OA (n=7). That overexpression could also be confirmed on mRNA level (2.0 fold, RA tissue n=4, OA tissue n=5). Moreover, in RASF, the constitutive mRNA level of PTPN2 was higher than in OA synovial fibroblasts (OASF) (1.6 fold, p<0.01, n=10-16). Stimulation with inflammatory cytokines such as TNFα (3.1 fold, p<0.05, n=4), TNFα and IL-1β (2.3 fold, n=5), LPS (1.9 fold, n=5) and hypoxia (1.3 fold, n=3) resulted in a further increase in PTPN2 mRNA levels. We found a 2.0 fold higher PTPN2 protein expression in RASF compared to OASF (n=4), and a 1.7±0.4 fold induction of PTPN2 in RASF after TNFα stimulation (n=4) by densitometric analysis of Western blot signals. IL-6 production increased 2.1 times in PTPN2 deficient cells (mean±SD pg/ml 11159±5179 vs. 24400±12801, n=4) compared to scrambled control. We could not see this effect concerning IL-8 production (35450±20619 pg/ml vs. 24148±24450 pg/ml, n=4). TRAIL-induced apoptosis increased by 34% after PTPN2 silencing (n=5). The level of autophagy (LC3B-II) did not differ basally and after TNFα stimulation in scrambled control and PTPN2 silenced cells. However, in scrambled control transfected cells, the addition of Thapsigargin induced the expression of LC3B-II protein (2.07±0.97 fold, n=5), indicative for autophagy. PTPN2 silencing reduced the induction of autophagy to 0.8±0.2 fold (n=5) compared to scrambled control. Conclusions: Since levels of autophagy are lower in PTPN2 silenced RASF compared to scrambled control, it is indicated that increased PTPN2 protein expression in RASF induces inflammation and elevated autophagy in RASF. Acknowledgements: This work was supported by IMI BTCure, IAR, Masterswitch-FP7 and ZIHP. Disclosure of Interest: None Declared